Heuristic evaluation on mobile halal detection application - Ahmad Hasan Ridwan; Irfan Safrudin; Muhammad Ali Ramdhani; Diena Rauda Ramdania (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
As a country with the largest Muslim population in the world, the halal status of a food and beverage product is essential for the people of Indonesia. An application was created by the government to answer these concerns with the name "Halal MUI". Unfortunately, this application has not been able to meet the needs of users to get a rating of 3.5 out of 920 users. This study aims to provide an evaluation of the Halal MUI application by using a heuristic evaluation approach. As many as three experts did a personal heuristic evaluation, then summarized it in a group discussion forum. The results showed that the application of Halal MUI, in general, has been able to check the halal product. However, some features still have a high severity rating. This paper presents several suggested improvements to improve system usability in Halal MUI applications.